Impacts of Marcellus Shale gas extraction: Examining recollected pre-development and post-development perceptions. Issue 4 (November 2020) - Theodori, Gene L.; Podeschi, Christopher W.
Highlights: Examined recollected pre- and post-development perceptions of shale development Overall pattern of recollected pre- and post-development perceptions mirrored previous findings Statistical analyses revealed differences between recollected pre- and post-development perceptions Abstract: Using data drawn from random samples of residents in and around two boroughs located in Lycoming County, Pennsylvania, we examined individuals' recollected pre-development and post-development perceptions of selected issues associated with Marcellus Shale development. Descriptive statistics revealed that the pattern of residents' recollected pre-development and post-development perceptions was more or less the same. In general, issues that residents perceived would worsen prior to the development of natural gas (recollected pre-development perceptions) were viewed as worsening after the upstream activities began (post-development perceptions). The same pattern held for those issues that residents had perceived would improve. Paired sample t-tests were used to determine whether any statistically significant differences existed between residents' recollected pre-development and post-development perceptions. Results revealed that the mean scores for residents' recollected pre-development and post-development perceptions differed significantly for the overwhelming majority of issues.